2011
DOI: 10.3109/09638288.2011.571333
|View full text |Cite
|
Sign up to set email alerts
|

Art after stroke: the qualitative experience of community dwelling stroke survivors in a group art programme

Abstract: The implementation of an arts health programme after stroke made a substantial impact on well-being and QOL. Results from this study are promising and this is a model that warrants rigorous investigation regarding the impact of art on QOL and wellbeing. This study also highlighted the need for community resources to address community re-integration and service provision in the form of age appropriate, activity-based groups for stroke survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(108 citation statements)
references
References 27 publications
8
96
0
Order By: Relevance
“…However, some stroke survivors experience continuing Accepted by The Arts in Psychotherapy, March 2012 14 frustration in using the stroke-affected hand in their art-making (Beesley et al,201). Several studies have reported that art therapy promotes increases in social interaction and social recognition of the stroke survivors' artistic abilities and competence (Beesley et al, 2011;Johnson & Sullivan-Marx, 2006;Kim et al, 2008;Symons et al, 2011;Yaretsky & Levinson, 1996). Emotional benefits include the experiences of pleasure, challenge, achievement, freedom and flow, as well as taking pride in developing artistic skills and artwork (Beesley et al, 2011;Horovitz, 2005;Johnson & Sullivan-Marx, 2006;Symons et al, 20011;Wald, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, some stroke survivors experience continuing Accepted by The Arts in Psychotherapy, March 2012 14 frustration in using the stroke-affected hand in their art-making (Beesley et al,201). Several studies have reported that art therapy promotes increases in social interaction and social recognition of the stroke survivors' artistic abilities and competence (Beesley et al, 2011;Johnson & Sullivan-Marx, 2006;Kim et al, 2008;Symons et al, 2011;Yaretsky & Levinson, 1996). Emotional benefits include the experiences of pleasure, challenge, achievement, freedom and flow, as well as taking pride in developing artistic skills and artwork (Beesley et al, 2011;Horovitz, 2005;Johnson & Sullivan-Marx, 2006;Symons et al, 20011;Wald, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Emotional benefits include the experiences of pleasure, challenge, achievement, freedom and flow, as well as taking pride in developing artistic skills and artwork (Beesley et al, 2011;Horovitz, 2005;Johnson & Sullivan-Marx, 2006;Symons et al, 20011;Wald, 1999). Another recurring finding is that art therapy enables stroke survivors to express their concerns symbolically, discharging feelings of anger, loss and abandonment, and achieving new insights (Beesley, et al 2011;Carmi & Mashiah, 1996;Gonen & Soroker 2000;Horovitz, 2005;Kim et al, 2008;Moon 2009;Sell & Murrey, 2006;Wald 1999;Wilson, 2001). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations